Characterization and Screening Phytochemicals Orange Purut Leaves (Citrus hystrix) Extract from Kampar, Riau - Wijiyaningsih, Dinda; Ridwanto, Ridwanto; Yuniarti, Rafita; Pulungan, Ainil Fithri (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2025)
Orange purut leaves (Citrus hystrix) are one of the shrubs that have high economic value because they contain vitamin C and are often used as a food flavoring. The aim of this research is to determine whether orange purut leaf extract contains phytochemicals and to characterize the properties of orange purut leaf extract. Phytochemical screening of orange purut leaf extract (Citrus hystrix) included the examination of flavonoids, tannins, saponins, steroids/triterpenoids, alkaloids, and glycosides. Phytochemical screening was conducted on both simplicia powder and simplicia extract, and characterization of the simplicia was carried out. The water content of orange purut leaves was found to be 8%, the water-soluble juice content was 37.9%, the ethanol-soluble juice content was 19%, the total ash content was 7.6%, and the acid-insoluble ash content was 0.6%. Orange purut leaf extract positively contains alkaloids, flavonoids, saponins, tannins, steroids/triterpenoids, and glycosides.